A review of the nutritional challenges experienced by people living with severe mental illness: a role for dietitians in addressing physical health gaps. Issue 5 (17th April 2017) - Teasdale, S. B.; Samaras, K.; Wade, T.; Jarman, R.; Ward, P. B.
Abstract: People experiencing a severe mental illness (SMI), such as schizophrenia, schizoaffective disorder, bipolar affective disorder or depression with psychotic features, have a 20‐year mortality gap compared to the general population. This 'scandal of premature mortality' is primarily driven by preventable cardiometabolic disease, and recent research suggests that the mortality gap is widening. Multidisciplinary mental health teams often include psychiatrists, clinical psychologists, specialist mental health nurses, social workers and occupational therapists, offering a range of pharmacological and nonpharmacological treatments to enhance the recovery of clients who have experienced, or are experiencing a SMI. Until recently, lifestyle and life skills interventions targeting the poor physical health experienced by people living with SMI have not been offered in most routine clinical settings. Furthermore, there are calls to include dietary intervention as mainstream in psychiatry to enhance mental health recovery. With the integration of dietitians being a relatively new approach, it is important to review and assess the literature to inform practice. This review assesses the dietary challenges experienced by people with a SMI and discusses potential strategies for improving mental and physical health.